The Effect of the Provision of Bagea Enriched with Sea Urchin Gonads on Weight Gain in Toddlers of the Bajo Ethnic - La Banudi; Suriana Koro; Muhammad Anas Anasiru; Nurmiaty Nurmiaty (Faculty of Public Health Universitas Indonesia, 2021)
Cassava starch extract and sea urchin gonads can be used as ingredients for making various kinds of food formulas. This study is expected to be able to develop cassava starch extract as a formula for making bagea added with sea urchin gonads which are rich in nutrients to make it good for pregnant women. This study was aimed at analyzing the effect of the provision of bagea enriched by sea urchin gonads on weight gain in toddlers of the Bajo community. In making the formula of bagea, the researchers used a quasi-experimental design. After the data were collected, they were then checked for feasibility, coded, and reduced. Furthermore, data were presented in tabular form, showing percentage and frequency, and analyzed using statistical tests. Consuming bagea enriched with sea urchin gonads has an effective effect on weight gain in toddlers of the Bajo tribe (p = 0.000). Furthermore, the provision of additional food from a government program (in form of biscuits) has also an effect on weight gain in toddlers of the Bajo tribe (p = 0.000). Apart from that, the researcher also found a difference between the consumption of bagea enriched with sea urchin gonads and the provision of additional food (biscuits) from the government program on weight gain in toddlers of the Bajo tribe (p = 0.000). Therefore, the proposed suggestion for health workers (nutrition improvement programmers) is that they should use bagea as one of the additional feeding interventions to improve nutritional status (weight gain) in toddlers.